Acute enlargement, morphological changes, and rupture of intracranial infectious aneurysm in infective endocarditis. Serial imaging. (December 2020) - Boukobza, Monique; Naggara, Olivier; Duval, Xavier; Laissy, Jean-Pierre
Highlights: Intracranial infectious aneurysms (IIAs) can show rapid increase in size, morphological changes. Rapid transformation over time, with the risk of rupture of IIAs, is unpredictable. Necessity of repeated imaging follow-up (Angio-CT, MRA) in IE patients under antibiotic therapy. If IIA shows rapid growth with serial imaging, it should be treated without further delay. Abstract: A 72-year-old man received a transcatheter aortic valve implantation (TAVI) 2 years ago for leakage of the degenerative bioprosthesis with Corevalve n°31 implantation, presented infective endocarditis (IE) (streptococcus sanguinis) of the bioprosthetic aortic valve. One month after antibiotic treatment was initiated, he presented a left-sided hemiplegia, a right frontal hematoma. MRI/contrast-enhanced magnetic resonance angiography (CE-MRA) revealed 2 infectious intracranial aneurysms (IIAs) of the right (10 mm) and left middle cerebral artery (MCA) (M2 segment, 5 mm). The right MCA IIA was treated within 1 day by glue-embolization. Seven days later, the patient acutely developed motor aphasia. CE-MRA showed significant enlargement (15 mm) and morphologic change of the ruptured left MCA IIA. This IIA was treated with Onyx-embolization. This case adds additional evidence that IIAs, during IE, can show rapid growth and morphological change over a 7 day course and emphasizes the imperative need of close imaging follow-up when IIAs are managed by antibiotic therapy.